Sustainable Tuna Supply Chain in Thailand: Challenges and Overcoming the Profitability Tradeoff - Karanapakorn, Nicha (2016)
In the industry of processed seafood, there has been a major issue of sustainability which is growing among the producers, sellers, and consumers. Overfishing has been causing shortages of fish stock, leading to a demand for more efficient management from the parties along the supply chain. Numerous academic efforts are made regarding sustainability in tuna industry concerning scientific aspects in fishing technology and certain tuna species. In addition, Thailand is the world’s major tuna processor for export, which makes it an excellent country to base as an example of the sustainability issues in the tuna supply chain. The author hopes to offer another view from the perspective of Thai tuna exporters on the challenges from which the call for sustainability in tuna among the scandals about slavery, conservation for tuna species, and price fluctuation due to demand shift have affected the company and the overall tuna industry in Thailand, along with the response of the tuna product processors in coping with the issues. This dissertation aims to understand changes in the demand for sustainability in the Thai tuna industry through the view of the tuna processors and how it affects them, including the response to the dynamic of the Thai government sector, the processing sector, and the change in their supply chain management. The study also aims to explore various types of actors in the industry, offer a different view of seeing the sustainability practices as a long-term solution to overcome the tradeoff of sustainability and profitability of the company through the perspective of the Sand Cone model theory by examining and analyzing their causal relationship with one another, and how they can become a complement which tuna exporters ought to possess. In order to achieve the objective of looking through the eye of tuna processors, an insightful interview has been conducted with the Managing Director of Pataya Food Industries, one of the largest tuna product exporters in Thailand, to gain the insight of the shift in the world tuna supply and how the change in the market demand in terms of sustainability has affected the company in reality. The author also has an objective to identify ways that the company can improve to adjust with the dynamic market.